2020
DOI: 10.1136/gutjnl-2019-319693
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid composition regulates GPR119-dependent intestinal lipid sensing and food intake regulation in mice

Abstract: ObjectivesLipid mediators in the GI tract regulate satiation and satiety. Bile acids (BAs) regulate the absorption and metabolism of dietary lipid in the intestine, but their effects on lipid-regulated satiation and satiety are completely unknown. Investigating this is challenging because introducing excessive BAs or eliminating BAs strongly impacts GI functions. We used a mouse model (Cyp8b1–/– mice) with normal total BA levels, but alterations in the composition of the BA pool that impact multiple aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 46 publications
4
53
0
Order By: Relevance
“…Loss of Cyp8b1 resulted in lower amounts of 12OH-BAs, including CA, a highly efficient BA in mixed micelle formation for dietary fat and cholesterol absorption [ 21 , 22 ]. Thus, lack of CA will result in slowing lipid hydrolysis and allowing lipid access to the lower intestine, which slows gastric emptying and reduces food intake via the gut hormones, GLP1 and PYY mediated GPR-119 signaling pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Cyp8b1 resulted in lower amounts of 12OH-BAs, including CA, a highly efficient BA in mixed micelle formation for dietary fat and cholesterol absorption [ 21 , 22 ]. Thus, lack of CA will result in slowing lipid hydrolysis and allowing lipid access to the lower intestine, which slows gastric emptying and reduces food intake via the gut hormones, GLP1 and PYY mediated GPR-119 signaling pathway [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the study by Higuchi et al, which identified mechanisms of increased satiation in Cyp8b1−/− mice via slowed gastric empting. 1 Following data showing that deleting Cyp8b1, which is required to produce 12α-hydroxylated bile acids, impaired intestinal lipid absorption in mice, the authors convincingly demonstrated that lowering 12α-hydroxylated bile acids slowed gastric emptying in Cyp8b1−/− mice. 1 Duodenal lipid infusion affects gastric function, and duodenal hypersensitivity to lipids has been studied in GI disorders with gastric dysmotility, such as functional dyspepsia (FD).…”
Section: Association Between Duodenal Bile Salts and Gastric Emptyingmentioning
confidence: 99%
“…1 Following data showing that deleting Cyp8b1, which is required to produce 12α-hydroxylated bile acids, impaired intestinal lipid absorption in mice, the authors convincingly demonstrated that lowering 12α-hydroxylated bile acids slowed gastric emptying in Cyp8b1−/− mice. 1 Duodenal lipid infusion affects gastric function, and duodenal hypersensitivity to lipids has been studied in GI disorders with gastric dysmotility, such as functional dyspepsia (FD). 2 FD is defined by upper GI symptoms originating from the gastroduodenal region with no structural disease on routine investigation.…”
Section: Association Between Duodenal Bile Salts and Gastric Emptyingmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the effects of bile acids on appetite regulation, particularly via the secretion of gastrointestinal hormones, it is intuitively likely that modulating bile acid signaling affects energy balance. Genetic ablation of the bile acid synthesis enzyme CYP8B1, leading to a deficiency of 12α-hydroxylated bile acids (e.g., CA), has been shown to be associated with reduced energy intake and subsequent weight gain in mice fed a fat enriched diet [ 48 , 49 ]. However, these effects appeared to be secondary to impaired fat hydrolysis and the increased exposure of unabsorbed fat to the distal gut, as in these mice, there was an increase in energy intake when fed a fat-free diet [ 49 ].…”
Section: Effects Of Bile Acid Signaling On Energy Intake and Body Weightmentioning
confidence: 99%